Assessment of Awareness of Legal Duties of School Personnel in Secondary Schools in Kebbi State, Nigeria - Manga, Sani Dantani (NIU Journal of Social Sciences; Vol 4 No 4 (2018): KIU Journal of Social Sciences, Vol. 4 No. 4, December 2018, 2019)
This paper assessed the awareness of legal duties of school personnel in secondary schools in Kebbi State, Nigeria. The paper raised three research questions focusing on legal duties of teachers, school administrators and students. In conducting this study a descriptive survey design was used. A validated instrument titled: Assessment of Legal Duties of School Personnel Questionnaire (ALSPQ) with a reliability index of 0.83 was used to collect. A population of 400 participants from four Education Zones of Kebbi State made up of 20 Principals and 60 Vice Principals was deliberately selected, while 120 Teachers and 200 Students were selected by Stratified and Simple Random Sampling Techniques. The instrument was based on a 4 point Likert Scale with Criterion Mean of 2.50 for acceptance and rejection. Mean Set was used to determine Rank Order of items while Aggregate Mean Set was used to decide on the level of awareness. The findings indicated that teachers, principals and students had a good awareness of their legal duties. The paper therefore recommended the continuous improvement of awareness of legal duties through seminars; workshops; training of school principals on Education Law as well as updating Students Handbook to upgrade rules and penalties for violation. Keywords: Legal Duties, School Personnel, Awareness, Education Law.